Performance Analysis of a Hybrid Security Algorithm for Secure Cloud Environment - Lukusa, John Mulopwe; Hocanın, Fatma Tansu (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Encryption algorithms are critical in ensuring the security of information in today's rapidly evolving internet and network applications. These algorithms are especially important in ensuring information security for internet-based dynamic applications and storage methods like cloud computing, which require high reliability, scalability, and autonomy to enable ubiquitous access. Given the prevalence of cloud computing in our everyday routines, data security has emerged as a major concern, particularly for non-technical users. To address this concern, the effectiveness of two widely used symmetric key encryption algorithms, AES and Blowfish, in terms of throughput, power consumption, and encryption speed, has been analyzed and compared. Based on the simulation results, it is clear that AES outperforms Blowfish when security flaws are put into consideration. It should be noted, however, that AES requires more processing power. As a result, a proposed efficient hybrid security algorithm seeks to combine the benefits of both approaches in an encryption system, thereby improving data security in a cloud environment while optimizing resource utilization. According to the performance analysis, the proposed hybrid approach is an excellent solution for encrypting and decrypting files with large block sizes and longer keys, as well as defending against Man in the Middle (MitM) attacks.